Inverse identification processes of elastoplastic constitutive models using advanced optimisation strategies - Coelho, Bernardete (2020)
The success of simulation tools in reproducing the mechanical behaviour of materials, particularly for metals, depends on the quality of the models and their inherent material parameters. However, the commonly used parameter identification strategies are still expensive and non-robust. The robustness and efficiency of these strategies are closely related with the single-stage optimisation methods adopted. The aim of this work is to implement and analyse optimisation strategies such as sequential, parallel and hybrid approaches in a parameter identification problem using full-field methods, particularly the Virtual Fields Method (VFM) and the Finite Element Model Updating (FEMU). The definition of the objective functions of both VFM and FEMU methods is also discussed in the framework of optimisation.